2013
DOI: 10.1016/j.ajpath.2013.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Development of Abdominal Aortic Aneurysm Is Decreased in Mice with Plasma Phospholipid Transfer Protein Deficiency

Abstract: Plasma phospholipid transfer protein (PLTP) increases the circulating levels of proatherogenic lipoproteins, accelerates blood coagulation, and modulates inflammation. The role of PLTP in the development of abdominal aortic aneurysm (AAA) was investigated by using either a combination of mechanical and elastase injury at one site of mouse aorta (elastase model) or continuous infusion of angiotensin II in hyperlipidemic ApoE-knockout mice (Ang II model). With the elastase model, complete PLTP deficiency was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…[9][10][11] Systemic PLTP deficiency in mice is also associated with a reduced thrombotic response 12 and reduced abdominal aortic aneurysm. 13 In rabbits, overexpression of PLTP-increased atherosclerotic lesions after a high-fat diet feeding when compared with controls. 14 In general, PLTP is a risk factor of atherosclerosis in animal models.…”
mentioning
confidence: 99%
“…[9][10][11] Systemic PLTP deficiency in mice is also associated with a reduced thrombotic response 12 and reduced abdominal aortic aneurysm. 13 In rabbits, overexpression of PLTP-increased atherosclerotic lesions after a high-fat diet feeding when compared with controls. 14 In general, PLTP is a risk factor of atherosclerosis in animal models.…”
mentioning
confidence: 99%
“…22,23 Finally, in a recent study from our group, the expression level of IL-6 and the number of infiltrating macrophages in aortic tissue after the induction of experimental aneurysm were lower in PLTP-deficient mice than in WT mice, providing additional support for the anti-inflammatory effect of PLTP deficiency in mice. 24 With regard to human studies, Cheung 11 and PLTP activity was found to be significantly increased in patients with bacterial infections and systemic inflammation. 25 In the present work, we observed that neither the total WBC counts nor the CD3 1 -cell subpopulations were modified in a PLTP-deficient context.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen content, elastin fragmentation and media SMC accumulation were graded according to the grading keys that were described previously. 29,30 CD31-positive microvessels, Ki67-positive cells, T cells, mast cells, and apoptotic cells were counted manually in a blinded fashion and presented as numbers per aortic arch section. Images of the relative macrophage and MHC-II contents within the aortas were captured by a Microscope VS120 Whole Slide Scanner (Olympus) and quantified by measuring the immunostaining signal-positive areas using computer-assisted image analysis software (Image-Pro Plus; Media Cybernetics, Bethesda, MD).…”
Section: Methodsmentioning
confidence: 99%